Pengaruh Current Ratio dan Debt to Equity Ratio terhadap Return on Equity pada Perusahaan Sub Sektor Otomotif yang terdapat di BEI tahun 2017-2021 - Uswatun Khasanah; siti nurcahayati (JURNAL KONSISTEN, 2024)
Purpose. This research aims to determine the influence of the Current Ratio and Debt to Equity Ratio on Return on Equity in Manufacturing Companies listed on the BEI in 2017-2021. Methods. This research is a quantitative research type. The sampling technique used was purposive sampling. The sample for this research is automotive sub-sector companies listed on the IDX in 2017-2021. The data analysis technique uses multiple linear regression. Results. This research proves that there is a stimulant influence between the Current Ratio and Debt to Equity Ratio on Return on Equity of 23.6%. Implications. The Current Ratio and Debt to Equity Ratio have a simultaneous effect on Return On Equity, which means that if the Current Ratio and Debt to Equity Ratio increase, this will be followed by an increase in Return On Equity.